Factors affecting critical screw-driving torques in particleboard - Tor, Onder; Yu, Xiaohong; Demirel, Samet; Hu, Lingling; Zhang, Jilei (BioResources, 2019)
Factors influencing the vertical driving force magnitude applied to screws during the process of driving the screws into faces of particleboard materials were investigated. In particular, the screw penetration depth and screwdriver air pressure were evaluated relative to critical torques, such as seating and stripping torques. Experimental results indicated that vertical driving forces significantly affected the magnitude of critical driving torques when no pilot hole was drilled, but this influence became non-significant when 3.2-mm diameter pilot holes were drilled. Screw-driving power had no significant effect on the magnitude of critical driving torques in particleboard materials if no pilot hole was drilled, but if pilot holes were drilled, increasing the screwdriver air pressure from 0.45 to 0.62 MPa led to increases in stripping torques. Increasing the screw penetration depth from 12.7 to 19.1 mm can significantly increase seating and stripping torques.